Distant lymph nodes serve as pools of Th1 cells induced by neonatal BCG vaccination for the prevention of asthma in mice. Issue 3 (25th January 2013) - Zhang, G.; Wang, P.; Qiu, Z.; Qin, X.; Lin, X.; Li, N.; Huang, H.; Liu, H.; Hua, W.; Chen, Z.; Zhao, H.; Li, W.; et al.
Abstract Background Neonatal Bacillus Calmette–Guérin (BCG) vaccination induces vigorous T‐helper type 1 (Th1) responses and inhibits allergy‐related airway dysfunction, but the exact mechanisms remain unclear. The objective of this study was to address where the Th1 cells induced by neonatal BCG vaccination are generated and stored, and how they are recruited into the inflamed airway for the prevention of allergen‐induced airway inflammation. Methods We vaccinated neonatal C57BL/6 mice with BCG in a mouse model of asthma and analyzed the expression and function of Th1 cells in vivo and in vitro. Results BCG vaccination–induced Th1 cells in the local inguinal lymph nodes (ILN) migrated into the lungs upon inhaled ovalbumin (OVA) challenge in OVA‐sensitized mice. These CD4+ T cells in the ILN exhibited potentials of activation, proliferation and cytokine secretion and expressed high levels of CXCR3. Adoptive transfer of CD4+ T cells from BCG‐treated ILN significantly decreased allergic airway responses. In addition, the protective effect of BCG vaccination against allergic airway inflammation was lost upon the excision of the ILN. Conclusions These data demonstrate that ILN serves as a 'weapon' pool of Th1 cells following BCG vaccination, and these cells are ready for the migration into the inflamed lungs upon the allergen challenge, thereby inhibiting allergen‐induced airway disorder.